Development of the Integer Operations E-Module I-Spiringsuite in Junior High Schools in Makassar City, South Sulawesi - Latri Aras; Rahmawati Patta; Ramlan Mahmud (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
his type of research is research and development which aims to describe the development process of the integer arithmetic operations e-module, describe the quality of the e-module based on the level of validity, practicality and effectiveness, and show the specifications of the integer arithmetic operations e-module. The e-module development process refers to the ADDIE model which includes 5 stages, namely analysis, design, development, implementation , and evaluation . The product trial respondents were students in class VII 2 MTs Makassar City with a total of 20 students. The research results show that the validator's assessment of the e-module and research instruments received an average score of 4.18 with valid criteria. The results of the questionnaire data analysis of teacher responses to the e-module obtained an average score of 1.89 with the criteria being fully implemented and the learning implementation observation sheet showed a score percentage of 91.7% so that the e-module was declared practical. The results of the analysis of student response questionnaire data showed very good criteria with a percentage of 95.6%, student activity sheets obtained a percentage of 91.8% with very positive criteria, and the learning achievement test reached 90%, so that the integer counting operation e-module declared effective. Referring to the analysis results obtained, it can be concluded that the integer calculation operations e-module can be used in learning activities.